2020
DOI: 10.21873/anticanres.14195
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Prognostic Nutritional Index Predicts the Development of Deep Venous Thrombosis After Pancreatic Surgery

Abstract: Background/Aim: Pancreatic surgery is associated with a high risk of developing deep venous thrombosis (DVT) and malnutrition. We aimed to evaluate the factors predicting the development of DVT, focusing on nutrition assessment tools. Patients and Methods: One hundred patients who underwent pancreatic surgery were postoperatively examined for DVT. We assessed the risk factors for the development of DVT after surgery. Results: Postoperative DVT was detected in 11 patients (11%). Patients who developed DVT after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a study about PNI prognosis in patients with high-grade serous ovarian cancer (HGSC), Zheng et al found that a low preoperative PNI (< 45.45) was associated with an advanced FIGO stage, increased CA125 level, more extensive ascites, residual disease and platinum resistance 28 . In general, the cutoff value of PNI fluctuated between 45 to 57 according to the already published researches [29][30][31][32][33] . Refining the cutoff value for different cancer type and individual patients is an area of active research.…”
Section: Discussionmentioning
confidence: 99%
“…In a study about PNI prognosis in patients with high-grade serous ovarian cancer (HGSC), Zheng et al found that a low preoperative PNI (< 45.45) was associated with an advanced FIGO stage, increased CA125 level, more extensive ascites, residual disease and platinum resistance 28 . In general, the cutoff value of PNI fluctuated between 45 to 57 according to the already published researches [29][30][31][32][33] . Refining the cutoff value for different cancer type and individual patients is an area of active research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is well recognised that hypercoagulable state, stasis and endothelial injury contribute to the development of thrombosis. Patients with vascular endothelial injury caused by malnutrition may develop venous thrombosis through the aggregation of platelets or the release of cytokines from subendothelial tissue (Iguchi et al 2020 ). Clinical evidence has shown that both hypoalbuminemia (Duman et al 2019 ; Acharya et al 2020 ) and lymphocytopenia (Kuplay et al 2020 ; Yeung et al 2021 ) are related to a high incidence of thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has shown that both hypoalbuminemia (Duman et al 2019 ; Acharya et al 2020 ) and lymphocytopenia (Kuplay et al 2020 ; Yeung et al 2021 ) are related to a high incidence of thrombus. Iguchi et al found that preoperative PNI was a significant risk factor for the development of deep vein thrombosis after pancreatic surgery (Iguchi et al 2020 ). In this study, we observed that thrombus accounted for 77.4% (123/159) of adverse perioperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that high-fat diet maintains high endogenous thrombin potential, which is associated with venous and arterial thrombosis independently of obesity and insulin resistance [31]. However, the correlation of nutritional status and VTE risk could be complex, since recent studies showed that the poor nutrition status was also associated with a high risk of developing DVT, particularly for those who underwent major surgeries [32,33]. Further studies are needed to elucidate the mechanisms underlying the association between MetS and DVT.…”
Section: Discussionmentioning
confidence: 99%